Принудительный выкуп земельных участков в публичных интересах как форма прекращения права собственности - Yefremowa, Inna (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The study aims at an evaluation of the compulsory purchase of the land in the public interest in regards to the article 35 of the Constitution of the Russian Federation. The author present the compulsory purchase in the public interest, including land, as a form of the property right limitation, that should fulfil the selected, established law procedures.